Tinjauan Hukum Ekonomi Syariah dan Analisis”UU.No.8,tahun 1999 Tentang Perlindungan Konsumen Terhadap Akad Istisna’pada Konveksi Musly Group - Khairul Bahri Nasution, Ahyar Azhari Lubis, Resi Atna Sari Siregar, (Islamic Circle, 2021)
The sale and purchase contract in the form of an order is called bai istisna’, one of the implementations of buying and selling orders is in convection. As for the fact that the practice of istisna’ at the Musly Group convection is in fact still experiencing delays in what was agreed upon. The order agreement mechanism is carried out by means of the buyer visiting the clothing maker directly or through electronic media, with the specifications desired by the consumer. The payment mechanism for the order is done by giving an order down payment as a binder, and the rest can be paid at the end when the buyer receives the ordered goods. However, in this case, the Convection party made a delay that was detrimental to the consumer. The Consumer Protection Law as its purpose is to protect the interests of consumers and serve as a warning to business actors has been regulated in Article 16 concerning actions that are prohibited by business actors. The implementation of the goods order contract at the Musly Group convection has fulfilled the pillars and conditions, but it is fasid in terms of default or negligence which in Islamic law is subject to compensation or dhaman al aqd.